Socioeconomic Factors as Predictors of Entrepreneurial Behaviour in Poultry Farm - Isiorhovoja, R.A. (Mediterranean Journal of Social Sciences, 2013)
This paper sets out to assess the effect of socioeconomic factors on the likelihood of respondent being a poultry farmentrepreneur. The 275 poultry farms registered with the Livestock department of Delta State Ministry of Agriculture, DeltaState, Nigeria, was the population studied. Data on socio-economic characteristics of poultry farmers and their relationship withthe farms were collected with the aid of questionnaire. Data obtained were analyzed using descriptive statistics and binarylogistic regression. The results revealed that the ages of respondents ranged from 18 to 68 years with a mean of 43.91 yearsand a standard deviation of 9.29; the age group 38 - 47 years had the highest frequency of poultry entrepreneurs (39.60%).Majority of poultry operators (42.18%) had either a diploma or certificate of education. Other findings were that age, gender,number of years of study and nature of parents’occupation were socio-economic factors which significantly affect the likelihoodof the respondent being a poultry farm entrepreneur. The authors recommend that entrepreneurial development programmesshould take cognizance of these factors in their design.